(untitled) (The Research of Medical Science Review, 2025)
Background: Using the wrong medicine is dangerous for patients, and this danger often increases in emergency departments because things happen so quickly. Because of their role in dispensing medications, a nurse’s knowledge, attitude and way of working strongly affect whether medication errors occur and are reported. Aim: This study aimed to evaluate the effectiveness of a structured nursing intervention in improving the knowledge, attitude, and practice of nurses regarding medication errors in the emergency department of a tertiary care hospital. Methods: A quasi-experimental pre-post design was employed with 54 ED nurses at Hayatabad Medical Complex, Pakistan. Participants underwent a 3-day intervention comprising lectures, case studies, and hands-on demonstrations on ME prevention. Validated KAP questionnaires were administered pre- and post-intervention. Data were analyzed using paired t-tests and chi-square tests via SPSS v27, with significance set at p < 0.05. Results: The study involved 54 nurses, primarily female (63%) and mostly aged between 26–30 years (46.3%). The majority had 1–3 years of experience (46.3%) and held a BSc in Nursing (55.6%). Following the intervention, there were statistically significant improvements in knowledge, attitude, and practice (KAP) scores, with paired t-tests confirming increases in knowledge (from 4.78 to 5.83), attitude (from 31.24 to 33.44), and practice (from 5.59 to 6.41), all with p-values < 0.001. Educational level was significantly associated with all three KAP domains. Conclusion: Nurses’ knowledge, attitude and practice about medication mistakes improved quite a lot after the intervention. Regular education and favorable institutional rules help keep medication safety practices from declining.